Within-day test–retest reliability of the 6-min walk test in patients with pulmonary fibrosis. Issue 2 (23rd February 2017) - Bloem, Ada E.M.; Veltkamp, Marcel; Custers, Jan W.H.; Dolk, Hanneke M.; Grutters, Jan C.; Spruit, Martijn A.
Interstitial lung diseases (ILDs) are a group of more than 150 different disorders characterized by inflammation of the lung parenchyma, or interstitium, often followed by the occurrence of pulmonary fibrosis. Patients with pulmonary fibrosis complain about exertional dyspnoea, exercise intolerance and reduced quality of life [1]. Poor exercise tolerance and oxygen desaturation during exercise are associated with poor survival [2]. Therefore, measuring exercise capacity in patients with pulmonary fibrosis is an important element of clinical management. The 6-min walk test (6MWT) is one of the most widely used clinical tests of functional exercise capacity in people with pulmonary fibrosis [3, 4]. One 6-min walk test may not be enough to obtain the best 6-min walk distance in patients with pulmonary fibrosis http://ow.ly/cVfK3082RIL